Concept App Development for National Library of Virtual Manipulatives (NLVM): An Initiative - Islam, ABM Rezbaul; Bullock, Emma (Journal of Education and Training, 2022)
An NSF-supported project, the National Library of Virtual Manipulatives (NLVM), was started in 1999 to develop a library of entirely interactive and web-based virtual manipulatives or concept tutorials. It was mainly in Java applets for mathematics instruction (K-12 emphasis). The NLVM was a resource to develop mathematics classrooms from which teachers could independently draw upon. The materials were also significant in the mathematical training of both in-service and pre-service instructors. However, twenty years later, with the proliferation of touch-screen devices, this fantastic resource is in a crisis of becoming lost to future generations. It has been seen that many computers no longer run Java. Besides, the older version of Java used in the initial advancement of the NLVM is no longer supported. Hence, it is the right time to rethink the NLVM for current, widely available touch screen devices. This is essential to bolster the offerings for both prekindergarten, K- 12, and university settings. Keeping the situation in mind, we have constructed four virtual manipulative applications compatible with touch-screen devices based on the outdated java-script types of virtual manipulatives available through the NLVM. The four concept apps are being conducted with children in classroom settings starting in Spring 2021. It will allow for further revisions of the apps if necessary. Then, the apps from this project would be combined as part of a more significant, federally, or privately funded external grant proposal to re-imagine and broaden upon all the virtual manipulatives currently found in the NLVM.